Technical study for the production of portable dry baths made of fiberglass-reinforced resin - Rau, J.; Muñoz, R.; Chipana Cuadros, H. (Latin American and Caribbean Consortium of Engineering Institutions, 2018)
Description and standardization of the Sanilab dry bath production process based on resin and fiberglass to contribute to the increase of sanitation coverage in homes that lack of a public sewer system and the elimination of silos or septic tanks and other forms not suitable for eliminating excreta such as rivers, ditches, canals or other.
Estudio Técnico para la fabricación de Baños Secos Portátiles hechos a base de resina reforzada con fibra de vidrio
Keywords: Materials science; https://purl.org/pe-repo/ocde/ford#2.05.00